Membingkai ulang pengembangan profesional guru pemula: Menuju kerangka konseptual bertingkat - Song Xinling; Taufani C. Kurniatun; Abu Bakar (Universitas Pendidikan Indonesia, 2026)
Early-career teachers face a crucial transition period, marked by high professional demands, uneven support, and ongoing retention challenges. Several studies still view professional development as a linear process of induction and mentoring, thus underemphasizing the interaction among teacher agency, the school context, and broader structural conditions. This study aims to critically examine dominant conceptualizations of early-career teacher professional development and develop a more integrative framework. The study employed a systematic critical review using the PRISMA procedure of Scopus-indexed journal articles published since 2016 that discussed early-career teachers and professional development. The results revealed several key patterns: the dominance of compliance-oriented professional standards, the weakening of teacher agency in restrictive school environments, unequal access to mentoring and support, and the importance of core teaching competencies. The study also emphasized the increasing relevance of digital and hybrid mentoring models as more flexible forms of support. These findings suggest that early-career teacher professional development should be understood as a dynamic, multilevel process shaped by interactions among individual, school, and broader structural factors.